The Impact of Partnership in the Management of Family Businesses (Challenges of the Future, 2021)
Purpose and Originality: The purpose of the survey is to examine and understand interpersonal relationships and their impact on the quality of governance in family businesses. The aim is to present interpersonal relationships in family businesses, their causes and impact on the quality of management.Method: The aim of the article will review and presentation of interpersonal relationships in family businesses, their causes and impacts on the quality of work. We will present the positive and negative factors of interpersonal relationships and the causes of the conflict.Results: In establishing good interpersonal relationships have a major impact in the parent organization. For good result is important both mutual cooperation as well as a good flow of information.Limitations/Future Research: In any family business, they are aware that they are regulated interpersonal relations are important for the success of the organization. In this article, we will limit ourselves to interpersonal relationships and how they affect the quality of work in the organization. Restrictions only be seen in the insufficient amount of practical experience in this field of research.
Keywords: leadership; interpersonal relations; quality; family businesses; partnership; conflicts